PEMBERDAYAAN ANAK SD DALAM UPAYA PENINGKATAN KONSUMSI GARAM BERYODIUM DI DESA APUAN KECAMATAN SUSUT KABUPATEN BANGLI - Adhi K, Tresna; Widarini, N.P (Buletin Udayana Mengabdi; Vol 10 No 2 (2011): Jurnal Udayana Mengabdi, 2012)
Iodine deficiency disorder (IDD) is the most single common cause of preventable mental retardation and brain damage in the world. It decreases child survival, causes goiters, and impairs growth and development. Apuan Village, Bangli Regency is categorized as endemic areas (TGR=20,3%) according to the definition from Health Office reports of Bali Province in 2008. One of the approaches that might be worth considering in alleviating the problem is the empowerment of elementary school children in an effort to increase the consumption of iodized salt in household. This approach aimed at empowering children to provide information to their parents on iodized salt consumption. Community services activities were conducted from December 16 to 21 October 2010 in SD 1 and SD 3 Apuan involving 62 elementary school children. The main activities were the provision of knowledge and guidance to elementary school children about the benefits of iodized salt. The first phase of the activities consists of examining the level of iodine in salt. This phase was then followed by giving the students a pre-test prior to the guidance and a post-test after the guidance for measuring the level of improvement on knowledge of elementary school children about iodized salt. The second phase was conducted one week after the first phase by measuring the level of iodine in the household salt of the same respondents. Data were analyzed using descriptive and analytical by computer program. Results pre-test and post-tests showed an increase in the knowledge for good knowledge category (0% to 31%), and moderate knowledge category (3.2% to 40.3%) and while a decrease in the limited knowledge category (96.8% to 9.7%). Statistical analysis showed significant differences (p <0.05). Test results that contain iodine salt showed increased percentage of 72.6% in the first phase to 96.7% in the second phase. It can be concluded that elementary school children might become a good initiator to improve the consumption of iodized salt in household. It is recommended to use an interesting or entertaining media in order to conduct health education so that the information provided is more easily absorbed and understood.